Piezoelectric responsive reinforced and toughened composite material as well as preparation method and application thereof

By introducing piezoelectric responsive composite materials into enhanced toughening materials, combined with functionalized processing of space electric field, the challenges of existing materials in taking into account both antibacterial and mechanical properties are solved, and the long-term stable self-anti-bacterial and excellent mechanical properties of the materials are achieved.

CN119868657AActive Publication Date: 2025-04-25PEKING UNIV SCHOOL OF STOMATOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510113057.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

Existing reinforced toughening materials have challenges in both antibacterial and mechanical properties, especially in oral clinical applications, where materials are easily invaded by bacteria, resulting in secondary caries and periimplant disease.

Method used

A piezoelectric responsive reinforcement toughening composite material is used, which consists of organic polymer materials and inorganic piezoelectric materials. By forming a three-dimensional network structure and promoting coupling of binding units, combined with functionalized processing of space electric field, the toughening and antibacterial effects of the material are achieved.

Benefits of technology

It realizes the long-term stable self-anti-bacterial and excellent mechanical properties of the material, which can effectively prevent bacterial invasion, enhance the toughness and crack resistance of the material, while maintaining the stability of electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868657A_ABST
    Figure CN119868657A_ABST
Patent Text Reader

Abstract

The invention discloses a piezoelectric responsive reinforced and toughened composite material as well as a preparation method and application thereof. The piezoelectric responsive reinforced and toughened composite material comprises an organic polymer material and an inorganic piezoelectric material, wherein the organic polymer material and the inorganic piezoelectric material are respectively communicated to form a three-dimensional network structure. According to the piezoelectric responsive reinforced and toughened composite material, the mechanical property of the material is also considered while the electrical property is considered, and experimental results prove that the piezoelectric responsive reinforced and toughened composite material has excellent piezoelectric responsiveness and electrical stability, meanwhile, synergistic toughening and reinforcement of the material are achieved, and the piezoelectric responsive reinforced and toughened composite material has a good application prospect. The method is high in operability in clinical application and can be used for developing biomedical materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of toughness materials, and in particular to a piezoelectric responsiveness enhanced toughening composite material and a preparation method and application thereof. Background Art

[0002] Reinforced and toughened materials refer to a type of material that can significantly improve its toughness and crack resistance while increasing its hardness or strength. This property makes reinforced and toughened materials widely used in many fields, such as construction, automobiles, aerospace, electronic communications, and medical devices. In these fields, materials not only need to withstand stress with a certain intensity, but also have sufficient toughness to resist deformation and fracture, thereby ensuring the safety and reliability of the product.

[0003] In oral clinical applications, implant abutments, inlays, crowns and other restorations generally do not have antibacterial properties and are easily invaded by oral bacteria, inducing secondary caries or peri-implant disease and causing damage to supporting bone tissue. The restorations eventually fall off or break due to insufficient supporting bone tissue. Therefore, researchers hope to prevent the occurrence of secondary caries and peri-implant disease by preventing bacterial invasion through restorations with self-antibacterial properties. Existing research mainly uses surface treatment of materials to exert antibacterial effects, but surface treatment is easily affected by the oral environment and has poor long-term stability.

[0004] Research on strengthening and toughening materials in the prior art has made certain progress. For example, by adding diene or polyene crosslinking agents to participate in the copolymerization of methyl methacrylate, the flexural strength of the material can be improved to a certain extent. However, this method often leads to increased brittleness of the material and reduced impact resistance, that is, it is difficult to strike a balance between strength and toughness. In addition, there is a method of utilizing the interaction between polyol polymers and connecting units to effectively improve the toughness and strength of the material by forming a connecting structure and a closed-loop structure interspersed between polymer chains. Although this method has achieved certain results, there are still certain challenges in terms of preparation process and cost control.

[0005] In summary, as a new type of material with both high strength and high toughness, reinforced and toughened materials have broad application prospects in many fields. However, there are still some problems and challenges in the preparation and application of reinforced and toughened materials with both antibacterial and mechanical properties in the existing technology, which requires researchers to continue to explore and innovate to promote the progress and development of materials science.

[0006] The information in the background technology is only for illustrating the general background of the present invention and should not be regarded as admitting or suggesting in any form that such information constitutes the prior art known to a person skilled in the art. Summary of the invention

[0007] In order to solve at least some of the technical problems in the prior art, the present invention provides a piezoelectric responsive reinforced toughened composite material and a preparation method and application thereof. Specifically, the present invention includes the following contents.

[0008] A first aspect of the present invention provides a piezoelectric responsive enhanced and toughened composite material, which includes an organic polymer material and an inorganic piezoelectric material, wherein the organic polymer material and the inorganic piezoelectric material are each connected to form a three-dimensional network structure, wherein the mass ratio of the organic polymer material to the inorganic piezoelectric material ranges from 1:10 to 1:200.

[0009] In certain embodiments, according to the piezoelectric responsive enhanced and toughened composite material described in the present invention, the inorganic piezoelectric material includes barium titanate, strontium titanate, barium strontium titanate, lithium niobate, potassium niobate, sodium potassium niobate, bismuth ferrite, bismuth titanate, calcium bismuth niobate, bismuth iron titanate, sodium bismuth titanate, barium sodium bismuth titanate, zirconium oxide, lanthanum oxide, cerium oxide, titanium dioxide, tantalum pentoxide, niobium pentoxide, calcium zirconate, barium calcium zirconate titanate, or at least one of the above-mentioned ternary or multi-component piezoelectric materials.

[0010] In certain embodiments, according to the piezoelectric responsive reinforced and toughened composite material of the present invention, the organic polymer material comprises an acrylic polymer.

[0011] In certain embodiments, according to the piezoelectric responsive reinforced and toughened composite material of the present invention, the reinforced and toughened composite material further comprises a bonding promotion unit, and the bonding promotion unit is coupled with the organic polymer material and the inorganic piezoelectric material, respectively.

[0012] In certain embodiments, according to the piezoelectric responsive reinforced toughened composite material of the present invention, the promoting binding unit is coupled with the organic polymer material and the inorganic piezoelectric material by reacting with a compound having the following structure: X(CH2) n SiY3 formula I, Wherein, n=0-3, X is selected from at least one of vinyl, amino, epoxy, methacryloxy, mercapto and urea, and Y is selected from at least one of chloro, methoxy, ethoxy, methoxyethoxy and acetoxy.

[0013] In certain embodiments, according to the piezoelectric responsive reinforced and toughened composite material of the present invention, the reinforced and toughened composite material has a porosity of 0.1-50%.

[0014] A second aspect of the present invention provides a method for preparing the piezoelectric responsive reinforced and toughened composite material as described above, comprising: (1) compacting the inorganic piezoelectric material and then sintering it to obtain a porous green body, wherein the compacting process includes dry-pressing the powder or particles of the inorganic piezoelectric material at 1-50 MPa for 1-120 s to form a preliminary shape, and then compacting it with a pressure medium at 50-500 MPa for 1-120 s to obtain a dense green body; (2) placing the sintered porous substrate in a solution containing an organic polymer material, and obtaining the reinforced and toughened composite material after curing.

[0015] In certain embodiments, according to the preparation method of the present invention, the sintering temperature is not less than 1000°C.

[0016] In certain embodiments, according to the preparation method of the present invention, the method further comprises the step of polarizing the reinforced and toughened composite material, with a polarization field strength of 0.1-5 kV / mm, a polarization temperature of 10-40°C, and a treatment time of 1-120 min.

[0017] In certain embodiments, the preparation method according to the present invention further comprises the step of treating the sintered porous substrate with a compound having the following structure: X(CH2) n SiY3 formula I, Wherein, n=0-3, X is selected from at least one of vinyl, amino, epoxy, methacryloxy, mercapto and urea, and Y is selected from at least one of chloro, methoxy, ethoxy, methoxyethoxy and acetoxy.

[0018] The third aspect of the present invention provides the use of the piezoelectric responsive reinforced and toughened composite material described in the present invention in the preparation of biomedical materials (including but not limited to oral prostheses, etc.) having both antibacterial properties and mechanical service properties.

[0019] The present invention achieves toughening and strengthening of composite materials by controlling the sintering temperature of piezoelectric materials and the ratio of inorganic piezoelectric materials to organic polymer materials. On this basis, the reinforced and toughened composite materials are subjected to spatial electric field functionalization treatment to form reinforced and toughened composite materials with different electrical strengths, while having excellent electrical and mechanical properties, and forming a long-term stable self-antibacterial electrical microenvironment. The reinforced and toughened composite materials prepared by the present invention are non-degradable, and the materials can maintain long-term stable electrical properties, which can avoid potential problems that harm the body, such as ion precipitation caused by material degradation and absorption by the human body.

[0020] In addition, due to its intrinsic ferroelectric properties, the reinforced and toughened composite material of the present invention can have different piezoelectric responsiveness after spatial electric field functionalization treatment. The established spatial electrical microenvironment can achieve stable and controllable soft tissue cell attachment and antibacterial effects. The antibacterial effect of the electrical microenvironment can achieve the effect of preventing bacterial invasion by enhancing the surface soft tissue closure and inhibiting the activity of surrounding bacteria. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The barium titanate reinforced toughened composites at different sintering temperatures before and after toughening are shown.

[0022] Figure 2 The results show the mass ratio of the organic polymer material to the piezoelectric material (barium titanate) in the material.

[0023] Figure 3 The flexural strength of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials is shown.

[0024] Figure 4 The elastic modulus of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials is shown.

[0025] Figure 5 The fracture toughness of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials is shown.

[0026] Figure 6 The XRD patterns of barium titanate substrates sintered at different temperatures are shown.

[0027] Figure 7 The flexural strength comparison between the barium titanate matrix sintered at 1200°C and the densely sintered barium titanate matrix before and after toughening with organic polymer materials is shown.

[0028] Figure 8 The elastic modulus comparison of the barium titanate matrix sintered at 1200°C before and after toughening with organic polymer materials and the densely sintered barium titanate matrix is ​​shown.

[0029] Fig. 9 The fracture toughness comparison of the barium titanate matrix sintered at 1200°C before and after toughening and the densely sintered barium titanate matrix is ​​shown.

[0030] Fig.10 Shown is the observation of cracks in a reinforced and toughened composite under nanoindentation.

[0031] Fig.11 It shows that the reinforced and toughened composite material can effectively generate piezoelectric signals under pressure.

[0032] Fig.12The three-dimensional structure image of the porous barium titanate matrix sintered at 1200°C is shown.

[0033] Fig.13 The results of electrical properties measurement of the reinforced and toughened composite materials after polarization treatment under different conditions are shown.

[0034] Fig.14 The electrical properties of the reinforced and toughened composite materials sintered at different temperatures after polarization treatment (A) and the electrical properties of the reinforced and toughened composite materials sintered at different raw material ratios after polarization treatment (B) are shown.

[0035] Fig.15 The results of measuring the cell spreading area and adhesion area on the surface of the reinforced and toughened composite material under pressure of different force values ​​are shown.

[0036] Fig.16 The results of cell proliferation and migration measurements on the surface of the reinforced and toughened composite material under pressure of different force values ​​are shown.

[0037] Fig.17 The experimental results of the antibacterial effect of the reinforced and toughened composite materials are shown. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] Reinforced and toughened composite materials One aspect of the present invention provides a piezoelectric responsiveness enhanced and toughened composite material. The piezoelectric responsiveness enhanced and toughened composite material of the present invention comprises a piezoelectric material as a matrix and an organic polymer material filled in the matrix, and the organic polymer material and the piezoelectric material are connected to each other to form a three-dimensional network (mesh) structure.

[0042] In the present invention, the inorganic piezoelectric material examples include, but are not limited to, barium titanate, strontium titanate, barium strontium titanate, lithium niobate, potassium niobate, potassium sodium niobate, bismuth ferrite, bismuth titanate, calcium bismuth niobate, bismuth iron titanate, sodium bismuth titanate, sodium bismuth titanate, barium bismuth titanate, zirconium oxide, lanthanum oxide, cerium oxide, titanium dioxide, tantalum pentoxide, niobium pentoxide, calcium zirconate, barium calcium zirconate titanate, or at least one of the above-mentioned ternary or multi-element piezoelectric materials. Those skilled in the art should understand that only some of the inorganic piezoelectric materials are listed above, and any inorganic piezoelectric material that can be used as a filling matrix for organic polymer materials can be used in the present invention.

[0043] The inorganic piezoelectric material of the present invention may be in the form of powder, granules or fibers. In the case of granules, the particle size is not particularly limited and may be 10 nm-200 μm, for example, 100 nm-150 μm, 500 nm-150 μm, 1 μm-150 μm, 50 μm-150 μm.

[0044] Not subject to any theoretical constraints, any organic polymer material that can be cured (such as but not limited to photocuring, thermal curing, etc.) in a porous inorganic piezoelectric material matrix can be used for the reinforced toughening composite material of the present invention, and its examples include but are not limited to acrylate polymers (copolymers), polyurethane polymers, organic polymer compounds containing two or more epoxy groups, and phenolic polymers. In the present invention, the organic polymer material includes acrylate polymers, and examples of acrylate polymers include but are not limited to methyl methacrylate, ethyl methyl acrylate, ethyl ethyl acrylate, and butyl acrylate, etc. A mixture of one acrylate polymer or two or more acrylate polymers can be used. When a mixture of two or more acrylate polymers is used, the ratio between the two or more acrylate polymers is not particularly limited and can be adjusted as needed. The molecular weight and viscosity of the acrylate polymer are not particularly limited, and those skilled in the art can select an acrylate polymer of suitable molecular weight and viscosity as needed.

[0045] In a preferred embodiment, the acrylic polymer used in the present invention is a methacrylic polymer, which includes but is not limited to methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, butyl methacrylate, and benzyl methacrylate. In a specific embodiment, the acrylic polymer used in the present invention is a mixture of bisphenol A glycerol dimethacrylate and triethylene glycol dimethacrylate.

[0046] In the present invention, the inorganic piezoelectric material first forms a porous matrix in the reinforced toughening composite material, and then the organic polymer material is fully filled in the pores. The present invention has found through a large number of studies that in such a three-dimensional network structure, the mass ratio of the organic polymer material to the inorganic piezoelectric material affects the mechanical properties of the reinforced toughening composite material, and further affects its electrical properties. The mass ratio of the organic polymer material to the inorganic piezoelectric material is too high. Although it can meet the toughness requirements, the elastic modulus and flexural strength are greatly reduced, and its electrical properties are greatly reduced. On the other hand, the mass ratio of the organic polymer material to the inorganic piezoelectric material is too low. Although it can improve the elastic modulus of the composite material, it will cause the toughness and flexural strength of the composite material to decrease, so that it cannot be applied to biomedical materials (including but not limited to oral prostheses, etc.).

[0047] In the present invention, the mass ratio of the organic polymer material to the inorganic piezoelectric material ranges from 1:10 to 1:200, preferably 1:10 to 1:150, further preferably 1:10 to 1:145, further preferably 1:10 to 1:100, further preferably 1:10 to 1:50, for example 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50.

[0048] In the three-dimensional network structure of the piezoelectric responsive reinforced toughened composite material of the present invention, a promoting binding unit connecting the organic polymer material and the piezoelectric material is further included, and the promoting binding unit is coupled with the organic polymer material and the inorganic piezoelectric material respectively. In a preferred embodiment, the promoting binding unit is coupled with the organic polymer material and the inorganic piezoelectric material by reacting with a compound having the following structure: X(CH2) n SiY3 formula I, Wherein, n=0-3, X is selected from at least one of vinyl, amino, epoxy, methacryloxy, mercapto and urea, and Y is selected from at least one of chloro, methoxy, ethoxy, methoxyethoxy and acetoxy.

[0049] In a specific embodiment, the compound used in the present invention is 3-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0050] Those skilled in the art will appreciate that the purpose of the present invention can be achieved without using any compound, that is, without any binding-promoting unit in the three-dimensional structure.

[0051] In the present invention, the reinforced and toughened composite material has a porosity of 0.1-50% before being filled with the organic polymer material, preferably 1-50%, further preferably 5-40%, further preferably 10-30%, and more preferably 10-20%.

[0052] Preparation method One aspect of the present invention provides a method for preparing a piezoelectric responsive reinforced and toughened composite material, comprising: (1) compacting the inorganic piezoelectric material and then sintering it to obtain a porous green body, wherein the compacting process includes dry-pressing the powder or particles of the inorganic piezoelectric material at 1-50 MPa for 1-120 s to form a preliminary shape, and then dry-pressing at 50-500 MPa for 1-120 s to obtain a dense green body; (2) placing the sintered porous substrate in a solution containing an organic polymer material, and obtaining the reinforced and toughened composite material after curing.

[0053] In a preferred embodiment, the preparation method of the present invention comprises: (1') compacting the inorganic piezoelectric material and then sintering it to obtain a porous green body, wherein the compacting process includes dry-pressing the powder or particles of the inorganic piezoelectric material at 1-50 MPa for 1-120 s to form a preliminary shape, and then compacting it with a pressure medium at 50-500 MPa for 1-120 s to obtain a dense green body; (2') treating the sintered porous green body (also referred to as a porous piezoelectric material or a porous substrate) with a reagent, wherein the reagent is a compound having the following structure, and the organic polymer material and the inorganic piezoelectric material are coupled by the reaction of the compound: X(CH2) n SiY3 formula I, wherein n=0-3, X is selected from at least one of vinyl, amino, epoxy, methacryloxy, mercapto and urea, and Y is selected from at least one of chloro, methoxy, ethoxy, methoxyethoxy and acetoxy; (3') treating the treated piezoelectric material in a solution containing an organic polymer material to obtain the reinforced and toughened composite material.

[0054] Those skilled in the art should understand that the purpose of the present invention can be achieved without the use of reagents for treatment, that is, the absence of a unit promoting bonding in the three-dimensional structure can also be achieved. This can be achieved by directly mixing the sintered material with a solution containing an organic polymer material and obtaining a reinforced and toughened composite material after curing.

[0055] Step (1') of the present invention is a compaction and sintering step, in which the piezoelectric material is first compacted, preferably comprising a first compaction and a second compaction step, wherein the first compaction comprises dry-pressing the powder or particles of the piezoelectric material at 1-50 MPa, preferably 5-50 MPa, and preferably 10-50 MPa (for example, 10, 20, 30, 40, 50 MPa) and maintaining it for 1-120 s, preferably 5-100 s, and preferably 5-50 s, and further preferably 10-50 s (for example, 10, 15, 20, 25, 30, 35, 40, 45, 50 s) to initially shape the green body. The second compaction includes using 50-500 MPa, preferably 60-250 MPa, preferably 80-200 MPa, and further preferably 100-200 MPa (e.g., 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200 MPa) after the first compaction. The pressure medium is compacted and maintained for 1-120 s, preferably 5-100 s, preferably 5-50 s, and further preferably 10-50 s (e.g., 10, 15, 20, 25, 30, 35, 40, 45, 50 s) to make the green compact dense and uniform. The pressure medium is not particularly limited and can be a liquid medium such as water. The compaction treatment temperature during the first compaction and the second compaction is not limited, preferably room temperature, and cold isostatic pressing is particularly preferred.

[0056] After compaction molding, further sintering treatment is performed. The inventors have found that the sintering temperature affects the mechanical properties of the reinforced toughened composite material, and further affects its electrical properties. The sintering temperature is too low (for example, not higher than 1000°C), although it can meet the toughness requirements, the elastic modulus and flexural strength are greatly reduced, and its electrical properties are greatly reduced. The reduced mechanical properties and electrical properties make it impossible to apply to biomedical materials (including but not limited to oral prostheses, etc.). On the other hand, the sintering temperature is too high (for example, not less than 1300°C), although it can improve the elastic modulus of the composite material, it will cause the toughness and flexural strength of the composite material to decrease, so that it is also impossible to apply to biomedical materials (including but not limited to oral prostheses, etc.). In a preferred embodiment, the sintering temperature is in the range of 1000-1290°C, preferably 1050-1290°C, further preferably 1100-1280°C, further preferably 1150-1250°C, for example 1150, 1160, 1170, 1180, 1190, 1200, 1210, 1220, 1230, 1240, 1250°C.

[0057] The heating method in step (1') is not particularly limited, and gradient heating can be used for sintering, for example, gradient heating within the range of 50-200°C, 80-180°C, 80-150°C or 80-120°C to a suitable temperature and then sintering to obtain a porous matrix.

[0058] Step (2') of the present invention is a step of treating the sintered porous substrate with a reagent, which comprises reacting a compound having formula (I), preferably a silane coupling agent, with water or a mixed solvent of water and alcohol under acidic conditions to obtain a coupling solution, and then keeping the substrate and the coupling solution under vacuum for a period of time, preferably 1-24 h, such as 1-12 h, 2-10 h, 2-8 h, 4-8 h, and vacuum drying at 40-90° C. (preferably 50-80° C., such as 50-70° C.) after the reaction.

[0059] When a mixed solvent of water and alcohol is used, the volume ratio of water, ethanol and the compound of formula (I) is 1-50:1-50:1, preferably 5-45:5-45:1, further preferably 5-30:5-30:1, further preferably 10-25:10-25:1, and more preferably 10-20:10-20:1.

[0060] Step (3') of the present invention is an organic polymer material filling and heat curing step. In order to fully infiltrate the substrate, the treated porous substrate and the organic polymer material are vacuum-assisted mixed and heat cured. The heat curing temperature and time are not particularly limited and can be adjusted according to the adaptability of the selected organic polymer material. In a preferred embodiment, the curing is performed at 80-200°C, preferably 80-180°C, preferably 80-160°C, and more preferably 80-150°C for 0.1-24 h, preferably 1-12 h, and more preferably 5-12 h.

[0061] The method of the present invention comprises the step of performing an optional corona poling treatment on the reinforced and toughened composite material, wherein the parameters of the corona poling treatment include: a polarization field intensity of 0.1-5 kV / mm, for example, 0.1-4 kV / mm, 0.1-3 kV / mm, 0.1-2 kV / mm, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2 kV / mm, etc. The polarization time is 1-120 min, preferably 15-90 min, such as 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90 min, etc.

[0062] application One aspect of the present invention provides the use of piezoelectric responsive reinforced and toughened composite materials in the preparation of biomedical materials (including but not limited to oral prostheses, etc.) having both antibacterial properties and mechanical service properties. Oral prostheses include but are not limited to implant bases, inlays, crowns, artificial teeth, bases, etc.

[0063] The reinforced and toughened composite material of the present invention has a broad spectrum of antibacterial properties, and can be used to inhibit or kill various bacteria, including Gram-positive bacteria represented by Streptococcus mutans or Gram-negative bacteria represented by Escherichia coli.

[0064] Example 1 1. Preparation method The barium titanate particles with a particle size of 30-100 μm are compacted, compacted and formed, and then sintered at a temperature interval of 100°C in the temperature range of 1000-1300°C to obtain a porous matrix. The compaction process includes a first compaction step and a second compaction step. The first compaction step includes: subjecting the barium titanate powder to dry pressing at 30 MPa and holding for 25 seconds to initially form a green body. The second compaction step includes using 180 MPa cold isostatic pressing after the first compaction and holding for 35 seconds to make the green body dense and uniform.

[0065] The substrate is subjected to coupling treatment, and the specific treatment steps include: mixing 45% volume of water, 45% volume of ethanol and 3% volume of silane coupling agent KH570, and adding acetic acid to adjust the pH to 3-4 to prepare a silane coupling solution, and then half immersing the barium titanate substrate in the solution, allowing the solution to fully infiltrate the substrate under vacuum assistance, and then completely immersing the substrate in the solution for 6 hours, and then taking it out and vacuum drying it at 60°C.

[0066] The coupled matrix is ​​filled with organic polymer material and heat-cured to achieve reinforcement and toughening of the piezoelectric material, wherein the organic polymer material is a mixture of bisphenol A propylene glycol dimethacrylate and triethylene glycol dimethacrylate (Bis-GMA / TEGDMA), and the mass ratio of the organic polymer material to the piezoelectric material ranges from 1:10 to 1:200.

[0067] Control group 1 (marked as porous barium titanate in the figure): The material of control group 1 uses barium titanate particles with a particle size of 30-100 μm, and after cold isostatic pressing, it is sintered at a temperature interval of 100°C in the temperature range of 1000-1300°C to obtain a porous matrix. The cold isostatic pressing treatment steps include: the barium titanate powder is subjected to 30 MPa dry pressing and maintained for 25 seconds to form a green body, and then 180 MPa cold isostatic pressing is used and maintained for 35 seconds to make the green body dense and uniform.

[0068] Control group 2 (marked as dense barium titanate in the figure): The material of control group 2 uses barium titanate particles with a particle size of 30-100 μm, which are cold isostatically pressed and sintered at 1400°C to obtain a dense barium titanate matrix. The cold isostatic pressing treatment steps include: the barium titanate powder is subjected to 30 MPa dry pressing and maintained for 25 seconds to form a green body, and then 180 MPa cold isostatic pressing is used and maintained for 35 seconds to make the green body dense and uniform.

[0069] For the materials before and after toughening, the flexural strength and elastic modulus of the materials were tested by three-point bending test, and the fracture toughness of the materials was tested by single-sided V-groove beam method. In addition, X-ray diffraction was also performed on the barium titanate matrix sintered at different temperatures.

[0070] 2. Results Figure 1 The pictures of barium titanate reinforced toughened composite materials at different sintering temperatures before and after toughening are shown, wherein the upper column is the barium titanate reinforced toughened composite material before toughening, and the lower column is the barium titanate reinforced toughened composite material after toughening.

[0071] Figure 2The mass ratio of the polymer to barium titanate in the material is shown. The mass ratio of the polymer to barium titanate can vary in the range of 1:10 to 1:200, wherein when the sintering temperature is 1200°C, the mass ratio of the polymer to barium titanate is between 1:35 and 1:36.

[0072] Figure 3 The flexural strength of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials is shown. The results show that the flexural strength of the barium titanate matrix is ​​significantly enhanced after toughening and strengthening with organic polymer materials. Among them, the barium titanate matrix sintered at 1200°C has the highest flexural strength after filling with organic polymer materials.

[0073] Figure 4 The elastic modulus of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials is shown. The results show that the barium titanate matrix sintered at 1200°C has an elastic modulus (16-20.3 GPa) closest to natural dentin after filling with organic polymer materials, which is beneficial to the downward transmission of occlusal force.

[0074] Figure 5 The fracture toughness data of the barium titanate matrix sintered at different temperatures before and after toughening with organic polymer materials are shown. The results show that the fracture toughness of the barium titanate matrix sintered at 1200℃ is higher after toughening. In summary, the barium titanate matrix sintered at 1200℃ has the best mechanical properties after toughening with organic polymer materials.

[0075] Figure 6 The XRD patterns of the barium titanate matrix sintered at different temperatures are shown. It can be seen that at the sintering temperature of the preparation method of the present invention, the crystal phase of the barium titanate matrix does not change, and the particles before sintering are all tetragonal.

[0076] Figure 7 The flexural strength comparison of the barium titanate matrix sintered at 1200°C before and after toughening and the densely sintered barium titanate matrix is ​​shown. The flexural strength of the barium titanate material toughened with organic polymer materials is significantly higher than that of the simple dense barium titanate matrix.

[0077] Figure 8 The elastic modulus of the barium titanate matrix sintered at 1200°C before and after toughening is compared with the densely sintered barium titanate matrix. The elastic modulus of the barium titanate material toughened with organic polymer materials is closer to natural dentin.

[0078] Fig. 9 The fracture toughness comparison of the barium titanate matrix sintered at 1200°C before and after toughening and the densely sintered barium titanate matrix is ​​shown. The fracture toughness of the barium titanate material toughened by organic polymer materials is equivalent to that of the dense barium titanate matrix.

[0079] Fig.10The cracks of barium titanate materials toughened by organic polymer materials were observed under nanoindentation, and crack bridging phenomenon of organic polymer materials can be seen at the cracks, which further clarifies the toughening mechanism of organic polymer materials enhancing the mechanical strength of barium titanate through crack bridging.

[0080] Fig.11 It shows that after the barium titanate matrix is ​​toughened and strengthened by organic polymer materials, it can still effectively generate piezoelectric signals under pressure. The present invention further constructs a three-dimensional structural image of the porous barium titanate matrix sintered at 1200°C through high-precision CT scanning, as shown in the figure. Fig.12 As shown, it can be seen that the pores are basically evenly distributed.

[0081] In summary, the mechanical strength of piezoelectric materials can be enhanced by adding organic polymer materials without significantly affecting the piezoelectric properties of the material itself.

[0082] Example 2 The reinforced and toughened composite material prepared in Example 1 was subjected to polarization treatment, and the polarization conditions were as follows: polarization time was 15-90 minutes, polarization field strength was 1 kV / mm, polarization medium was air, and polarization temperature was 25°C.

[0083] The results are as follows Fig.13 As shown in Figure A, the piezoelectric constant d of the reinforced toughened composite material after polarization for different time periods is shown in Figure 33 Figure B shows the surface potential data of the reinforced and toughened composite material measured after polarization for different times. The above results show that the residual polarization performance of the material can be regulated by controlling the polarization time. Figure C shows the piezoelectric signal image of the reinforced and toughened composite material under 200 N pressure after polarization for different times. Figure D shows the piezoelectric strength data of the reinforced and toughened composite material under 200 N pressure with different polarization times. The results show that the piezoelectric strength is positively correlated with the polarization time. Figure E shows the piezoelectric signal graph of the reinforced and toughened composite material under different pressures after 90 minutes of polarization. Figure F shows the piezoelectric strength data of the reinforced and toughened composite material under different pressures after 90 minutes of polarization. The results show that the piezoelectric strength is positively correlated with the applied pressure value. In summary, the polarization time can be adjusted to enable the reinforced and toughened composite material to achieve the required piezoelectric strength under different pressure conditions. The frequency of the pressure applied to the composite material in this embodiment is 1.5 times / second, which is the normal physiological chewing frequency of a person.

[0084] This example further polarizes the barium titanate substrate sintered at different temperatures for 90 minutes after being filled with organic polymer materials, and tests the piezoelectric voltage strength data under a pressure of 200 N. The results are as follows: Fig.14 As shown in Figure 2, the barium titanate matrix sintered at 1200°C can significantly improve the piezoelectric voltage strength after toughening compared with other temperatures (such as Fig.14(as shown in Figure A).

[0085] This example further polarized the reinforced and toughened composite materials with different raw material ratios for 90 minutes, and tested the piezoelectric voltage strength data under a pressure of 200 N. The results are shown in Fig.14 As shown in Figure B, different raw material ratios affect the piezoelectric properties of the reinforced and toughened composite materials. Among them, when the sintering temperature is 1200°C, the mass ratio of organic polymer material to piezoelectric material is 1:35 to 1:36, and the reinforced and toughened composite material has a significantly improved piezoelectric voltage strength.

[0086] Example 3 1. Effects of reinforced and toughened composites on gingival fibroblasts Gingival fibroblasts were inoculated on the surface of the reinforced and toughened composite material after 90 minutes of polarization. The reinforced and toughened composite material was subjected to pressure of different force values, and the pressure was applied 1200 times at a frequency of 1.5 times / second (half of the number of times a person chews daily). After 6 hours, the cell adhesion focal protein was immunofluorescently stained to measure the cell spreading area and adhesion focal area under pressure of different force values. The control group material was commercially available grade 4 pure titanium, and the size of the control group was consistent with that of the reinforced and toughened composite material.

[0087] The results are as follows Fig.15 As shown in Figure 1, it can be seen that the cell spreading area and focal adhesion area are the largest at about 100 N pressure (about 4.5 V) (Figure AB), and Figure C shows the ratio of focal adhesion area to cell spreading area. It can be seen that the ratio reaches the maximum at 100 N pressure. Figure D shows the quantitative spreading area of ​​gingival fibroblasts, which can be seen to be the largest at 100 N pressure.

[0088] 2. CCK-8 experiment on cell proliferation of reinforced and toughened composite materials Gingival fibroblasts were inoculated on the surface of the reinforced toughened composite material after 90 minutes of polarization. The reinforced toughened composite material was subjected to pressure of different force values, and the pressure was applied 2400 times at a frequency of 1.5 times / second every day. CCK-8 tests were performed at 1 day and 3 days. The control group material was commercially available grade 4 pure titanium, and the size of the control group was consistent with that of the reinforced toughened composite material.

[0089] The results are as follows Fig.16 As shown in Figure A, after 3 days, cell proliferation was significantly enhanced under 100 N pressure (about 4.5 V).

[0090] 3. Cell scratch test of reinforced and toughened composites Using a cell scratch healing plug-in, gingival fibroblasts were inoculated on the surface of the reinforced toughened composite material after 90 minutes of polarization. The reinforced toughened composite material was subjected to pressure of different force values ​​at a frequency of 1.5 times / second for 2400 times. After 1 day, the cell nucleus was stained to observe the healing of the scratch. The control group material was commercially available grade 4 pure titanium, and the size of the control group was consistent with that of the reinforced toughened composite material.

[0091] The results are as follows Fig.16 As shown in Figure B, it can be seen that the migration activity of cells is significantly enhanced under 100 N pressure (about 4.5 V).

[0092] 4. Antibacterial experiment of reinforced and toughened composite materials The common oral pathogen Streptococcus mutans was inoculated on the surface of the reinforced and toughened composite material after 90 minutes of polarization. The reinforced and toughened composite material was subjected to pressure of different force values, and the pressure was applied 1200 times at a frequency of 1.5 times / second. For the implant abutment, the marginal soft tissue sealing effect is more important than the antibacterial effect. In order not to affect the soft tissue integration effect of the composite material, the maximum force value was selected to be 100 N. The control group material was commercially available grade 4 pure titanium, and the size of the control group was consistent with that of the reinforced and toughened composite material.

[0093] The results of the antibacterial effect experiment are as follows Fig.17 As shown in Figure A, the number of bacterial colonies decreased significantly under the pressure of 50 N. The quantitative statistical results of the number of bacteria are shown in Fig.17 As shown in Figure B.

[0094] Streptococcus mutans was inoculated on the surface of the reinforced toughened composite material after 90 minutes of polarization. After 12 hours of incubation, the reinforced toughened composite material was subjected to pressure of different force values, and the pressure was applied 1200 times at a frequency of 1.5 times / second. The culture was continued for 12 hours, and crystal violet staining was used to quantify the formation of bacterial biofilm. The results were consistent with the antibacterial plate experiment. The bacterial biofilm was least formed under the pressure of 50 N (such as Fig.17 (as shown in Figure C).

[0095] After inoculating the common oral pathogen Streptococcus mutans on the surface of the reinforced and toughened composite material after 90 minutes of polarization, the reinforced and toughened composite material was subjected to pressure with different force values, and the pressure was applied 2400 times at a frequency of 1.5 times / second. The live and dead bacteria were stained and images were taken for 24 hours. The results matched the previous antibacterial experimental results (such as Fig.17 D).

[0096] In summary, the piezoelectric signal of the reinforced and toughened composite material has an obvious effect of promoting soft tissue adhesion, and at the same time can ensure a certain antibacterial effect, which can prevent the occurrence of oral secondary caries, peri-implant disease, etc.

[0097] The reinforced and toughened composite material provided by the present invention has strong operability in clinical application. During the application of the reinforced and toughened composite material, it exhibits excellent piezoelectric responsiveness and electrical stability, and realizes synergistic enhancement of mechanical reinforcement and toughening. While considering the electrical properties, the mechanical properties of the material are also considered, and the technical synergy of promoting cell adhesion, antibacterial and mechanical toughening is further realized, ensuring the feasibility of clinical use, and contributing to the development of biomedical materials, for example, it helps in the clinical prevention of secondary caries, peri-implant disease, etc. and the long-term stability of implants.

[0098] Although the present invention has been described with reference to exemplary embodiments, it should be understood that the present invention is not limited to the disclosed exemplary embodiments. Various adjustments or changes may be made to the exemplary embodiments of the present specification without departing from the scope or spirit of the present invention. The scope of the claims should be based on the broadest interpretation to cover all modifications and equivalent structures and functions.

Claims

1. A piezoelectric responsive reinforced and toughened composite material, characterized in that: It comprises an organic polymer material and an inorganic piezoelectric material, wherein the organic polymer material and the inorganic piezoelectric material are connected to form a three-dimensional network structure, wherein the mass ratio of the organic polymer material to the inorganic piezoelectric material is in the range of 1:10 to 1:

200.

2. The piezoelectric responsive reinforced and toughened composite material according to claim 1, characterized in that: The inorganic piezoelectric material includes barium titanate, barium strontium titanate, lithium niobate, potassium niobate, potassium sodium niobate, calcium bismuth niobate, bismuth ferrite, bismuth titanate, bismuth iron titanate, sodium bismuth titanate, sodium bismuth titanate, barium sodium bismuth titanate, lanthanum oxide, titanium dioxide, barium calcium zirconate titanate, or at least one of the above-mentioned ternary or multi-element piezoelectric materials.

3. The piezoelectric responsive reinforced and toughened composite material according to claim 1, characterized in that: The organic polymer material includes at least one of acrylic polymer materials selected from methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, butyl methacrylate, and benzyl methacrylate.

4. The piezoelectric responsive reinforced and toughened composite material according to claim 1, characterized in that: The reinforced and toughened composite material further comprises a bonding promotion unit, and the bonding promotion unit is coupled with the organic polymer material and the inorganic piezoelectric material respectively.

5. The piezoelectric responsive reinforced and toughened composite material according to claim 4, characterized in that: The coupling-promoting unit is coupled with the organic polymer material and the inorganic piezoelectric material by reacting with a compound having the following structure: X(CH2) n of the formula I, SiY3 Wherein, n=0-3, X is selected from at least one of vinyl, amino, epoxy, methacryloxy, mercapto and urea, and Y is selected from at least one of chloro, methoxy, ethoxy, methoxyethoxy and acetoxy.

6. The method for preparing the piezoelectric responsive reinforced and toughened composite material according to any one of claims 1 to 5, characterized in that: include: (1) compacting the inorganic piezoelectric material and then sintering it to obtain a porous green body, wherein the compacting process includes dry-pressing the powder or particles of the inorganic piezoelectric material at 1-50 MPa for 1-120 s to form a preliminary shape, and then compacting it with a pressure medium at 50-500 MPa for 1-120 s to obtain a dense green body; (2) placing the sintered porous substrate in a solution containing an organic polymer material, and obtaining the reinforced and toughened composite material after curing.

7. The method for preparing the piezoelectric responsive reinforced and toughened composite material according to claim 6, characterized in that: The method further comprises treating the sintered porous substrate with a compound having a structure of formula I.

8. The method for preparing the piezoelectric responsive reinforced and toughened composite material according to claim 7, characterized in that: The sintering temperature is not less than 1000°C.

9. The method for preparing the piezoelectric responsive reinforced and toughened composite material according to claim 7, characterized in that: The method further comprises the step of performing polarization treatment on the reinforced and toughened composite material, wherein the polarization field strength is 0.1-5 kV / mm, the polarization temperature is 10-40° C., and the treatment time is 1-120 min.

10. Use of the piezoelectric responsive reinforced and toughened composite material according to any one of claims 1 to 5 in the preparation of biomedical materials having both antibacterial properties and mechanical service properties.

Citation Information

Patent Citations

  • Composite ceramic material, and preparation method and application thereof

    CN106830928A

  • Piezoelectric composite material capable of being subjected to 3D printing / hot press molding and preparation method thereof

    CN114220912A

  • Conductive piezoelectric material and preparation method and application thereof

    CN116328033A